Pelatihan Teknik Perbanyakan Vegetatif Tanaman Hias pada Ibu-Ibu PKK di Desa Bokor, Tumpang, Kabupaten Malang - Kartika Yurlisa; Sudiarso Sudiarso; Nurul Aini; Sitawati Sitawati; Titin Sumarni; Cicik Udayana (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING ON VEGETATIVE PROPAGATION TECHNIQUES OF ORNAMENTAL PLANTS FOR PKK WOMEN IN BOKOR VILLAGE, TUMPANG, MALANG REGENCY. The Covid-19 pandemic that has hit the world in the last 2 years has harmed all sectors of human life. The Indonesian government issued a policy to reduce the activity and mobility of people outside the house to reduce the rate of transmission of the virus. This policy has hurt the people's economy. Activities that are only in the house environment can increase the potential for stress in the community. One solution to overcome the problems mentioned above is to cultivate ornamental plants in the yard of the house. The trend of ornamental plant cultivation has an impact on increasing the number of requests and prices of ornamental plants and it is directly related to the strengthening of the bargaining position of ornamental plant farming. Activities carried out include observation, training, practice of ornamental plant propagation and assistance, and evaluation. The vegetative propagation techniques used were leaf cuttings, stem cuttings, seedling separation, and a demonstration of grafting activities, which were carried out on 9 of ornamental plant species, namely sansevieria, zamioculcas, little hogweed, aglaonema, iris, carwx morrowii, spider ivy, dracaena, and codiaeum. The results of the activity showed that partner’s knowledge and skills in the vegetative propagation of ornamental plants increased by 19%. The participants were able to reproduce ornamental plants vegetatively well. The percentage of success in growing plants from partner propagation is 71.4-100%.